Coupled Geomechanics and Flow Modeling of Fractured Reservoirs considering Matrix Permeability Anisotropy. (22nd February 2022) - Wu, Dawei; Di, Yuan; Wu, Yu-Shu
Abstract : The effect of geomechanics is crucial in the modeling of fractured reservoirs since fractures can be more stress-sensitive than the rock matrix. In fractured reservoirs, the microscale fractures are often homogenized into the matrix continuum leading to matrix permeability anisotropy. The embedded discrete fracture model (EDFM) is becoming increasingly popular for numerical simulation of fractured reservoirs and has been successfully employed in the simulation of coupled geomechanics and flow systems. However, the anisotropic permeability of matrix cannot be considered in traditional EDFM. An approach of coupled geomechanics and flow modeling is proposed for fractured reservoirs considering anisotropic matrix permeability. In order to calculate the fluid exchange between fractures and rock matrix in an anisotropic formation, an integrally embedded discrete fracture model (IEDFM) is used. The geomechanics model of the proposed approach uses an equivalent continuum approach, which introduces an equivalent material to represent the overall deformation of the fractured rock under normal and shear stresses. The constitutive relations of the equivalent continuum are derived rigorously from stress-strain analysis, where the stress-dependent moduli of natural fractures are included. The coupled geomechanics and flow system is solved using the fixed-stress split iterative coupling strategy with the dynamic hydraulic parameters of matrix and fractures updated separately. Several examples are performed to demonstrate the applicability of the proposed approach for modeling the coupled geomechanics and flow system in fractured reservoirs considering anisotropic permeability. The effect of anisotropy is investigated, which indicates that the dynamic behavior of a fracture is highly orientation-related due to initial stress anisotropy and matrix permeability anisotropy. Simulations also show that the anisotropic matrix permeability affects the compaction in the reservoir domain, which reflects on the performance of production.